(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, there is a classification of pedagogical skills and the socio-pedagogical necessity of their development in teachers, improving the system of training pedagogues today, improving the skills of pedagogues, developing pedagogical skills and abilities. Each pedagogical ability has its own characteristics, and it is explained that it is necessary for a pedagogue to know them and to be able to develop these abilities.